Erfolgreich recherchieren - Wirtschaftswissenschaften - Pianos, Tamara; Pianos, Tamara; Krüger, Nicole (Erfolgreich recherchieren, 2014)
The volume Erfolgreich recherchieren - Wirtschaftswissenschaften provides a comprehensive overview of information resources in all sectors of economic sciences. The work not only presents key research tools such as library catalogues, specialized bibliographies, Internet search engines, article databases, and reference works, but also includes strategies for conducting a successful literature search.